1993
DOI: 10.1007/bf00114978
|View full text |Cite
|
Sign up to set email alerts
|

U-77,863: a novel cinnanamide isolated from Streptomyces griseoluteus that inhibits cancer invasion and metastasis

Abstract: Several cinnamoyl compounds have been shown to have antitumor activities, but not specifically anti-invasive or antimetastatic effects. U-77,863 (o-methyl cinnanamide) was originally isolated from a fermentation beer of Streptomyces griseoluteus and recently synthesized (Harper, DE and Welch DR. Journal of Antibiotics, in press). Based upon some differential activities of cinnanamides, in general, and U-77,863, specifically, we tested the hypothesis that U-77,863 could inhibit invasion and metastasis of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Multiple growth factors, including FGFs, EGF-related factors, TGFjSs, HGF, and vascular endothelial growth factor (perhaps acting through the FLK oncogene product), are thought to mediate angiogenesis (468,469). Some emerging antiangiogenic therapies target these growth factors with structural antagonists (470), while others, such as AGM1470 (now called TNP 470), do not have fully established mechanisms (471)(472)(473)(474). Chemotherapy seems to synergistically interact with this type of therapy (475).…”
Section: B Growth Factors Proteases Angiogenesis and Metastasismentioning
confidence: 99%
“…Multiple growth factors, including FGFs, EGF-related factors, TGFjSs, HGF, and vascular endothelial growth factor (perhaps acting through the FLK oncogene product), are thought to mediate angiogenesis (468,469). Some emerging antiangiogenic therapies target these growth factors with structural antagonists (470), while others, such as AGM1470 (now called TNP 470), do not have fully established mechanisms (471)(472)(473)(474). Chemotherapy seems to synergistically interact with this type of therapy (475).…”
Section: B Growth Factors Proteases Angiogenesis and Metastasismentioning
confidence: 99%
“…Cinnamamide derivatives display anticancer potential [17, 18], and can be linked with various moieties (such as phenyl, benzyl, or heterocyclic rings) while retaining their biological activity [1921]. As such, we prepared a series of derivatives of 6-cinnamamido-quinoline-4-carboxamide (CiQ) (Figure 1A, compound 5 ), which were designed as hybrid molecules consisting of a quinoline moiety and a cinnamamide core.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Wattenberg et al (1980) reported that naturally occurring phenolic derivatives of CINN, i.e., o-hydroxycinnamic acid, 3,4-dihydroxycinnamic acid (caffeic acid), and 4-hydroxy-3-methoxycinnamic acid (ferulic acid), suppressed benzo(a)pyrene-induced neoplasia of the forestomach. Recently, Welch et al (1993) have reported that several cinnanamide compounds isolated from Streptomyces griseoluteus inhibit cancer invasion and metastasis in the melanoma cell lines C8161 and A375 (M).…”
mentioning
confidence: 99%